SOCIAL MEDIA AND DEMOCRACY IN THE DIGITAL ERA: “DESAK ANIES” CAPTURING THE HEARTS OF YOUNG PEOPLE’S PARTICIPATION IN SOCIAL MEDIA - Satria, Teguh; Rahmawati, Dian Eka (JWP (Jurnal Wacana Politik), 2025)
This research aims to analyse the ‘Desak Anies’ political campaign strategy run by Anies Baswedan in the 2024 Indonesian General Election, focusing on the use of social media and direct interaction to increase young voter engagement. This research uses a qualitative method with a case study approach. Data collection was conducted through analysis of mass media sources, literature reviews, and interactions on Twitter social media, which were then processed using Nvivo 12 Plus software. The data analysis technique in this study uses an interactive model technique developed by Miles, Huberman, & Saldaña which consists of three stages, namely data reduction, data presentation and conclusion drawing. This research applies four main theories namely Democracy Theory, Political Communication, Social Media, and Political Participation to examine the impact of the campaign on political participation and public communication. The results show that ‘Desak Anies’ succeeded in creating active participation and open dialogue among young voters, but also revealed the limitations of social media in presenting political issues in depth and the risk of polarising opinions. The article also highlights the challenges of using social media in simplifying complex political issues and the risks of polarising opinions. Through this exploration, this article provides insights into the potential and limitations of social media as a tool for political mobilisation in the digital age.